Economic analysis of vocational high schools - YOON, Hee Ryoung (KDI School, 2017)
Since 2008 financial crisis, youth unemployment problem in Korea has seriously addressed in the society. The government pointed out that reducing a mismatch between workers’ skills and labor market’s demand is a critical factor to alleviate the matter, and this acknowledgment called forth to introduce or upgrade secondary vocational education programs such as Meister high school (MHS) and Specialized High School (SHS).This study aims to analyze cost-effectiveness and economic viability of MHS and SHS which are the current vocational high school types in Korea. The cost-benefit analysis and cost-effectiveness analysis will be used, the national level of samples covering public and private MHS and SHS from 2010 to 2015 will be studied. From the cost-effectiveness analysis, the research result pointed out that MHS is more cost-effectivenessregardingemployment rate than SHS. However, SHS is more cost-effective when it comes to the wage rate. Also, the study verifies that SHS is more economically viable than MHS by calculating Net Present Value (NPV). It allows us that we can say that SHS is more efficient and cost-effective in terms ofwage rate over MHS.
Thesis(Master) --KDI School:Master of Development Policy,2017